Problematika Pembelajaran Bahasa Indonesia bagi Siswa Kelas IV di Sekolah Dasar - Haryemi, Ifa (Fakultas Sastra Universitas Muslim Indonesia, 2023)
This study aims to find out the problems that occur in learning Indonesian in elementary schools, especially class IV SDN Gili Barat, Kamal District, Bangkalan Regency, East Java. Participants in this study were class IV teachers and 18 male students and 8 female students with a total of 26 students. Data collection techniques used in this study were observation, interviews, questionnaires and tests. The first step before observing learning in class, the researcher conducted a case study at school. Furthermore, researchers made observations of student learning in the classroom with the aim of observing the state of the class during direct learning. The instruments used by the researchers were interview sheets with class teachers, observation sheets in class, student questionnaires and oral tests in the form of reading material. The reading material used by researchers is reading text in student books with the title